Atropinic (Anticholinergic) Burden in Parkinson's Disease. Issue 5 (29th March 2016) - De Germay, Sibylle; Montastruc, Jean‐Louis; Rousseau, Vanessa; Chebane, Leila; Bondon‐Guitton, Emmanuelle; Moulis, Florence; Durrieu, Genevieve; Bagheri, Haleh; Rascol, Olivier; Pariente, Antoine; Bégaud, Bernard; Montastruc, François
Abstract: Use of atropinic drugs remains controversial in Parkinson's disease (PD) because there is insufficient evidence about their efficacy and they can induce serious adverse drug reactions. Atropinic risk scales were developed to help to identify atropinic drugs in prescription forms and to evaluate their burden in clinical practice. In the present review, we discuss the few studies investigating atropinic burden in PD and present the results of our study indicating that atropinic drugs are still widely prescribed in PD (almost 3 of 5 prescriptions) with a clinically significant atropinic burden in around 1 of 6 PD patients. Drugs mainly responsible for high values of atropinic burden were those used for nonmotor symptoms. Clinically significant atropinic burdens were mainly induced by associations of several "low‐risk" drugs. Physicians must be aware that in addition to classical atropinic antiparkinsonian drugs, many others (psychotropics) can contribute to increased atropinic burden in PD patients. © 2016 International Parkinson and Movement Disorder Society